The Challenges and Dilemmas of Spoken English Education in the Context of the Compulsory Education System in China - Li, Shuning (Transactions on Social Science, Education and Humanities Research, 2024)
Many students in China are disturbed by their inability to speak English fluently, and "dumb English" is a common phenomenon among English learners in China. There are some problems in spoken English education in the elementary education stage in China, which to a certain extent have led to the formation of this phenomenon. Taking English education in China's compulsory education stage as the background, this study conducted semi-structured interviews with four front-line English teachers in primary and junior high schools to gain an in-depth understanding of the current situation of English education and spoken English education, and to summarize the factors affecting teachers’ spoken English teaching and students' spoken English proficiency, from the perspectives of teachers, students, the education system, etc. The study found that teachers face problems such as their own weak spoken English ability and lack of teaching experience in spoken English; students often have problems such as inaccurate pronunciation and nonnative expressions; also, there may be some problems with the arrangement of curricula and teaching contents for every grade; in addition, factors such as over-emphasis on grades in exams, lack of funds and teaching resources, absence of a good language environment, and lack of attention from parents are all influencing teachers’ work on spoken English teaching and students' spoken English learning effect.